Teaching Diffusion Process to Children with Complex Communication Needs - Rahayu, Rindi Magneti; Hufad, Achmad; Sunardi; Nandiyanto, Asep Bayu Dani (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to teach the concept of the diffusion to students with special needs. This study used a single research approach with A-B design (baseline and intervention) in one of the inclusion Early Childhood Education in Bandung, Indonesia. The students of this study were five students who were diagnosed with obstacles in complex communication. The teaching method given in this research was an experimental demonstration to explain the phenomenon in the diffusion. Factors that can influence the diffusion process was also adjusted to the student’s condition. The results revealed that understanding concept of diffusion increased through teaching with experimental demonstrations. The increases in the understanding could reach up to about 60% after receiving treatment compared to the teaching with conventional way that can reach only about less than 10%. The atmosphere in the learning process can foster student curiosity. Indeed, students can be more focus in the ongoing teaching process. The repetition of student matter during the learning process is very helpful because the characteristics of the student that have difficulty in communicating, in which it requires direction and exposure of material that is simple and can be easily understood.